Evaluating the influence of old and new rental systems on the physical condition of historic mixed-use buildings: a case study of Lebanon - Sedki, Ali (Frontiers in Built Environment, 2023)
Abstract: This paper investigates the link between the built heritage physical condition and official local authorities’ legislation in Lebanon. The research analyses the impact of occupation on dwelling physical condition under the prevailing official inherited rental legislations, moreover, identifying the scale of the problem and the factors leading to it. The responsibilities of the Lebanese official bodies for renting legislation regarding historical buildings were thoroughly discussed. Also, a field survey for historical dwellings’ condition was conducted. To accomplish its objectives, the study employed a three-stage methodology. The first stage involves reviewing archival records, current legislation, and relevant literature to gain a comprehensive understanding of historical dwellings laws and regulations in Lebanon. The second stage is divided into two parts. First, the case study area of Yacob Al Labban historical square in Tripoli, Lebanon is selected and justified. This area will be examined to understand the impact of local authorities' legislation and rental regulations on the physical condition of historical dwellings. Second, a field survey will be conducted to gather specific information on building typology, physical condition, and building defects. This data will help establish a connection between legislation and buildings’ physical condition. In the third stage the findings will be analyzed, interpreted, and compared with existing literature to draw meaningful conclusions about the relationship between legislation and the condition of historical buildings in Lebanon. Research results revealed that there is a strong relationship between historical dwellings deterioration and renting legislations. Additionally, the study found that low rental fees were directly associated with a lack of maintenance across all types of rentals.